Transformasi Governansi Digital Dalam Meningkatkan Kualitas Pelayanan Publik Di Era Digital - Mozin, Sri Yulianty; Hardiyanto (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2026)
This study examines the transformation of digital governance in improving the quality of public services in the digital era. The rapid development of information and communication technology has encouraged governments to shift public service systems from conventional models to digital-based services that are more effective, efficient, transparent, and responsive. Digital governance transformation is implemented through the adoption of the Electronic-Based Government System (SPBE), e-government innovations, the use of public service applications, and the development of smart governance supported by artificial intelligence. The findings indicate that digital transformation has a positive impact on public service delivery, including faster administrative processes, improved bureaucratic accountability, strengthened transparency, and increased accessibility for citizens. However, this transformation also faces several challenges, such as limited technological infrastructure, insufficient digital competencies among government officials, unequal digital literacy within society, and difficulties in integrating systems across government institutions. Therefore, strengthening regulatory frameworks, improving human resource capacity, and expanding equitable digital infrastructure are necessary to ensure sustainable and effective digital governance transformation in enhancing public service quality.